SISTEM INFORMASI PENJUALAN DAN TRACKING PENGIRIMAN BARANG BERBASIS SMS GATEWAY PADA PT. MAPAN DJAYA PLASTIK - SATRIAWAN, HB, SIGIT SATRIAWAN; YULIANTON, HERIBERTUS (Information Technology and Telematics, 2018)
Abstract- PT. Mapan Djaya Plastik is a company engaged in the production of offering a variety of plasik bottle products. Currently the business process run by PT. Mapan Djaya Plastik is still manual in which the buyer must see the catalog itself in PT. Mapan Djaya Plastik and the information provided is only through word of mouth or use existing social networking. Another problem is the delivery system of goods that exist at this time tend to be still manual, that is customer contact to PT. Mapan Djaya Plastik to know the position of goods that have been shipped by PT. Mapan Djaya Plastik. System development method used in this research is prototype, system design using UML and system implementation using PHP, GAMMU and MySQL.The results in this study is a system of sales information and tracking delivery of goods based on SMS Gateway at PT. Mapan Djaya Plastik can identify problems related to the customer such as notification of transaction information via SMS automatically and tracking the delivery of goods with SMS format ORDER to see transaki goods and STATUS to see the status of delivery of goods Keywords – Sales, Tracking, PT. Mapan Djaya Plastik, PHP, GAMMU, MySQL DAFTAR PUSTAKA [1]    Budicahyanto, D. (2009) SMS Gateway,PT.Elex Media Komputindo,Jakarta [2]    Aditya, A.N, (2010), Jago PHP & MySQL Dalam Hitungan Menit, Dunia Komputer, Bekasi [3]    Prasetyo, D.D, (2006), Administrasi Database Server MySQL, Elex Media Komputindo, Jakarta. [4]   Wammu, (2017) GAMMU, http://wammu.eu/gammu/ diunduh pada tanggal 11-12-2017